“We are not like them”. The generational shift in leadership perceptions in an emerging market - Shapenko, Andrey; Dickmann, Michael; Horwitz, Frank Martin (Sage, 2026)
This study examines the evolving leadership identity among a new generation of Russian business leaders, challenging the temporal stability of static cross-cultural frameworks. Based on qualitative interviews with 30 MBA graduates in Moscow, Russia, the findings propose a model of hybrid leadership characterized by confidence, result-driven inspiration, relational care and ingenious concept of otvetstvennost (ownership and moral responsibility). The research reveals a significant shift in leadership perceptions, where emerging leaders favor participative, humane-oriented, and transformational leadership styles over traditional authoritarian approaches. However, this transition is marked by a sociolinguistic tension: a persistent reluctance to internalize the term “leader” despite demonstrating leadership behaviors. This generational shift is theorized as an identity struggle between entrenched national prototypes and global managerial exemplars. The implications suggest that leadership development in transitional economies functions as an “identity laboratory,” requiring programs that reconcile local cultural nuances with evolving global standards.
Keywords: leadership identity; social identity; culture; Russia; 35 Commerce, Management, Tourism and Services; Business & Management; 3505 Human resources and industrial relations; 3507 Strategy, management and organisational behaviour